Analysis on the Design of a Mobile Contextual Learning Mode - Lu, Wanyi (Journal of Theory and Practice of Contemporary Education, 2023)
The mobile situational learning mode has obvious contemporary characteristics. Essentially, it belongs to the learning mode derived from information technology scenarios, which is different from the outdated learning mode in the past. With the development of the times and the progress of technology, its functions are becoming more and more diverse, and it is deeply concerned and valued by contemporary teachers and students. Overall, the mobile situational learning model is not only beneficial for improving students' autonomous learning thinking, but also for enhancing their level of autonomous learning and enabling more people to have a good learning attitude. Next, this article will rely on the "Research and Construction of Mobile Contextual Learning Mode" to systematically study the value and characteristics of this mode, and combine the research results to analyze mobile learning technology, in order to explore solutions to create a mobile situational learning mode and provide more positive and beneficial references.